2016
DOI: 10.1016/j.dld.2016.06.028
|View full text |Cite
|
Sign up to set email alerts
|

HCV novel therapeutic regimens in Wonderland: A budget impact analysis in the Lombardy Region

Abstract: Treating HCV-infected persons in the Lombardy Region with the new drugs would reduce healthcare expenditure on this specific disease, in each forecast implemented, thus reducing the economic burden of the pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Among them, DAAs, for example, viral protease and NS5A inhibitors, can be reasonably regarded as the most promising drugs [10]. Drug pricing evolution in HCV and a budget impact analysis were described previously [11,12]. 75 Particularly, it was concluded that 'big pharma' use a value-based pricing model for HCV treatments.…”
Section: Aq4mentioning
confidence: 99%
“…Among them, DAAs, for example, viral protease and NS5A inhibitors, can be reasonably regarded as the most promising drugs [10]. Drug pricing evolution in HCV and a budget impact analysis were described previously [11,12]. 75 Particularly, it was concluded that 'big pharma' use a value-based pricing model for HCV treatments.…”
Section: Aq4mentioning
confidence: 99%
“…Nowadays, policy makers adopt Budget Impact Analysis (BIA) studies to estimate fiscal consequences of adopting new health technology or new medication (ISPOR, 2014). BIA estimates financial consequences of adopting a new health technology or intervention within a specific context (Garagiola, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their high efficacy, concerns have been raised about the costs associated with DAA therapy. With respect to the Italian scenario, different budget impact analyses have been published, however, considering only the drug cost19 or the complete treatment path 20. To date, no studies have investigated the actual cost sustained by the Italian National Health Service (NHS) during the first year of clinical use of second-generation DAAs.…”
Section: Introductionmentioning
confidence: 99%